Study of soil particles contaminated with radioactive cesium in pond sediment. Issue 1 (1st January 2019) - Ohnuma, Tohru; Ishii, Keizo
Abstract: The Fukushima Daiichi Nuclear Power Plant accident caused by the tsunami following the Great East Japan Earthquake in March 2011 resulted in contamination in Namie and Iitate, located in Fukushima Prefecture. These villages are in mountainous areas where achieving decontamination by removing soil is difficult. However, washout by rain is expected. The mountainous land is eroded by rainfall, so the soil will flow out into rivers and ponds. We assumed that polluted soils would have accumulated in ponds, and investigated the sediment to evaluate the mountain decontamination ability of rainfall. Although the surface of the pond sediment was radioactive, highly contaminated layers that were expected to have formed due to heavy rain immediately after the accident were not found. We recognized that the separation of the contaminated soils based on the particulate mean size was carried out in the pond.